Generación de modelos de caminata bípeda a través de diversas técnicas de modelamiento - Contreras Bravo, Leonardo Emiro; Vargas Tamayo, Luis Fernando (Ingeniería, 2005)
Many researchers have studied the modelling and simulation of the human march under two approaches: models of passive dynamics long walk, in which the gravity occurs to great importance in order that on the behaviour of a walker mechanism and the approach of this article in which active dynamics long walk will be showed,n in that exist actuators or elements that will provide energy to the system to obtain the long walk. The analysis will show from the simple thing to the complex, initiated with a model of inverted pendulum, happening through a model of a leg to arriving a five links model.For each one of the models, the dynamics analysis appears under techniques of Langrageana dynamics and the method of the graphs of union.The results of the five links models are validated comparing with results the others investigations